Law and Ethics for Pharmacy Technicians, 3rd Edition - Jahangir Moini (Cengage Learning, 2019)
A one-of-a-kind primer, LAW AND ETHICS FOR PHARMACY TECHNICIANS, 3rd Edition helps readers navigate the unique legal and ethical obstacles in pharmacy technician careers. Thought-provoking case studies engage students in the real-life legal and ethical dilemmas that could wreak havoc, instead emboldening them to step up, solve problems, and be stronger practitioners. In addition to understanding liability as it applies to pharmacy techs, chapters inform readers on state and federal regulations, HIPAA, workplace safety, ethics in pharmacy practice, and other key topics recommended by the Pharmacy Technician Certification Board (PTCB) and the American Society of Health System Pharmacists (ASHP). More than a text, LAW AND ETHICS FOR PHARMACY TECHNICIANS is a how-to guide for thriving in modern health care settings while preventing fraud, liabilities, and lawsuits.